Improve your grammar Essential guide to accurate writing - Jakeman, Vanessa; Peterson, Ken; Harrison, Mark (London Palgrave Macmillan, 2016)
Parts of speech - nouns, verbs, adjectives, prepositions, pronouns, articles, linking words and phrases